Correlation between local glucose transporter densities and local 3-O-methylglucose transport in rat brain - Duelli, Roman; Maurer, Martin H.; Staudt, Richard Erhard; Sokoloff, Louis; Kuschinsky, Wolfgang (Neuroscience letters, 2001)
The present study addresses the question whether local glucose transport kinetics are correlated with local glucose transporter densities in the brain. In 47 brain structures the local rate constants for 3-O-[14C]methylglucose (3-O-MG) transport, K1 and k2, were quantified, and local glucose Glut1 and Glut3 transporter densities were determined by immuno-autoradiographic methods. Statistically significant correlations were found between the rate constants for glucose transport and the transporter densities. The correlations were tighter for Glut1 than for Glut3. Inasmuch as 3-O-MG is transported by the same transporter as glucose, these results indicate that the local densities of glucose transporters determine local glucose transport rates in the brain.